Programming and Problem Solving with Python - Kamthane, Ashok; kamthane, Amit Ashok (Mc Graw Hill Education, 2020)
"The second edition of Programming and Problem Solving with Python is a hands-on-guide for engineering students from all streams, self-learners, and professionals to use Python language to perform complex calculations and write applications. The text is replete with programs and illustratively solved examples to explain all fundamental and theoretical concepts. The text develops problem-solving and code writing skills. This new edition is enhanced with new chapters, chapter-end and book-end projects and pedagogical elements while retaining the book’s original characteristics of lucid writing and illustrative explanation. All programs are thoroughly updated and checked for their compatibility with the latest versions of Python v3.8. KEY FEATURES • Three new chapters on GUI and Python Programming using Tkinter, MySQL Database and Exception Handling • New projects on Book Inventory Management, Employee Database Management etc. • Pedagogical Features 1. 180+ Multiple Choice Questions 2. 220+ True or False Questions 3. 90+ Exercise Questions 4. 100 Programming Assignments "